2018
DOI: 10.1039/9781788013116-00103
|View full text |Cite
|
Sign up to set email alerts
|

CHAPTER 4. Raman, IR and INS Characterization of Functionalized Carbon Materials

Abstract: Vibrational spectroscopies represent a powerful tool to investigate the structural properties at an atomic level. In particular, the analysis of the spectra allows to have detailed information on both structure and chemical environment of different sites. Therefore, the spectroscopic characterization can usefully assist in the comprehension of the parameters ruling the unique catalytic properties of metal-free carbon materials, as well as to implement the knowledge in the design of new C-containing systems. Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 114 publications
0
9
0
Order By: Relevance
“…Raman spectroscopy is one of the main analytical techniques that provide a detailed picture about chemical structure, phase, crystallinity and molecular interactions, not only of the CNTs and graphene sheets, but also of the final assembled fiber. A detailed description of CNT and graphene Raman features goes beyond the scope of this review and can be found elsewhere (Dresselhaus et al, 2010;Saito et al, 2011;Eckmann et al, 2012;Jain et al, 2017;Groppo et al, 2018). Among all fingerprints, the presence of the D-band at about 1350 cm −1 comes from double resonance Raman effect corresponding to disordered carbon structure, while the G-band (c.a.…”
Section: A-few Characterization Techniquesmentioning
confidence: 99%
“…Raman spectroscopy is one of the main analytical techniques that provide a detailed picture about chemical structure, phase, crystallinity and molecular interactions, not only of the CNTs and graphene sheets, but also of the final assembled fiber. A detailed description of CNT and graphene Raman features goes beyond the scope of this review and can be found elsewhere (Dresselhaus et al, 2010;Saito et al, 2011;Eckmann et al, 2012;Jain et al, 2017;Groppo et al, 2018). Among all fingerprints, the presence of the D-band at about 1350 cm −1 comes from double resonance Raman effect corresponding to disordered carbon structure, while the G-band (c.a.…”
Section: A-few Characterization Techniquesmentioning
confidence: 99%
“…The convoluted band in the region 2960-2850 cm −1 was attributed to the asymmetric (2930 cm −1 ) and symmetric (2850 cm −1 ) stretching of C-H on sp 3 hybridized carbons [60] . The band shown at 1720 cm −1 can be assigned to C = O stretching in carboxylic aids, lactones and/or acid anhydrides [41] , although its position in aromatic structures can be affected by the presence of the different proximal groups [61] .…”
Section: Spectroscopic Characterizationmentioning
confidence: 99%
“…However, the study of the additional contribution of D , D and D * bands, obtained by deconvolution of Raman spectra, using a combination of four Lorentzian and one Gaussian functions allows a more in depth analysis of the degree of order in graphene based carbons [69] . D band (around 1620 cm −1 ) is attributed to the "graphene-like" layers or sp 2 nanostructures with a strained geometry [61] , D band (around 1500 cm −1 ), whose intensity is inversely proportional to crystallinity, is observed between the G and D band [70] . The D * band (around 1250 cm −1 ) is originated from the vibration of carbon sp 3 atoms that were restricted by oxygencontaining groups [69] .…”
Section: Spectroscopic Characterizationmentioning
confidence: 99%
“…Raman spectra of magnetic carbon microspheres, obtained by means of three laser lines (785, 514, and 442 nm), are displayed in Figure 6. All the spectra are dominated by two intense bands, attributed to vibrational modes involving sp 2carbon species with a low sp 3 -carbon content commonly found in defective nanographitic crystallites (Ferrari and Robertson, 2000;Pimenta et al, 2007;Groppo et al, 2018). The signal around 1,600 cm −1 (G-band, E 2g symmetry), resulting from the in-plane bond stretching, is for a fact upward shifted of about 20 cm −1 with respect to the G-band of graphite, thus indicating that the stacking order of the sheets is very low and that the structure is also defective.…”
Section: Inner Structure Textural and Vibrational Properties Of The Magnetite-based Carbon Microspheresmentioning
confidence: 99%
“…The amorphous nature of the carbon structure for both carbon materials is also well-supported by the observed IR absorption band in the 1,620-1,450 cm −1 range, with a maximum at about 1,570 cm −1 (Supplementary Figure 4, left panel). Such IR band is, for a fact, associated with presence of double-conjugated C vibrational modes (ν C=C ) in sp 2 carbons in presence of defects (i.e., surface terminations, heteroatoms, functional groups, radical species, where there is a change of the dipole moment (in contrast to what observed in graphitic carbon materials, more ordered domains) (Jain et al, 2017;Groppo et al, 2018).…”
Section: Optical Properties Of the Samplesmentioning
confidence: 99%